Vitamin and mineral supplementation in athletes, with special reference to the ergogenic effects and possible toxic side-effects - Weight, Lindsay M (Division of Physiological Sciences, 2024)
The use of vitamin and mineral supplements as ergogenic aids is widespread amongst both athletes and the general population. Although there appear to be at least some theoretical reasons to suggest that supplementation may enhance athletic performance, there is limited scientific justification for this belief. There is also no evidence that the vitamin requirements of heavily training athletes eating a normal diet are ,_ increased. Furthermore, the possiblity that roxic side-effects may develop when high doses of vitamins and minerals are consumed, raises the question of the safety of this practice. This study was designed to answer the following questions:- (i) Does a commercially-available multi-vitamin and mineral supplement enhance the athletic performance of a group of trained marathon runners? ii) Do athletes require additional vitamin and minerals in view of their increased energy expenditure? (iii) Are there toxic side-effects associated with daily vitamin and mineral supplementation in these runners? A nine-month cross-over, placebo-controlled study design was employed. The subjects were 30 competitive male athletes who had been running for at least three years and who were training more than 70 km per week. They were randomly assigned to two groups, so that 15 received placebo